Measurement of naturally acquired humoral immune responses against the C-terminal region of the Plasmodium vivax MSP1 protein using protein arrays - Chen, Jun-Hu; Wang, Yue; Ha, Kwon-Soo; Lu, Feng; Suh, In-Bum; Lim, Chae Seung; Park, Jeong Hyun; Takeo, Satoru; Tsuboi, Takafumi; Han, Eun-Taek (Parasitology research (1987), 2011)
Protein arrays are powerful tools for antibody profiling and vaccine development against infectious agents. In the previous report, we successfully applied an antibody-based protein array for immunoprofiling of Plasmodium vivax infection. Herein, we developed a Ni-NTA surface based protein array to detect immune responses against the recombinant C-terminal region (19 and 42 kDa) of the P. vivax merozoite surface protein 1 (PvMSP1-19 and -42) from sera of vivax malaria patients. The PvMSP1-19 arrays detected P. vivax in 112 of 130 (86.2%; 95% CI, 83.2–89.2%) microscopically positive samples and 2 false positives were obtained among 100 sera samples from healthy subjects (2.0%; 95% CI, 0.6–3.4%). These results were in concordance with results of enzyme-linked immunosorbent assays (ELISA). Kappa values represented excellent agreement for the recombinant PvMSP1-19 protein against sera samples as measured by protein arrays and ELISA (Kappa = 0.904, 95% CI: 0.849–0.960). The PvMSP1-42 protein arrays detected antibody response in 100 of 130 microscopically positive samples (76.9%; 95% CI, 72.4–86.8%) and 8 false positives were obtained in 100 healthy subjects (8.0%; 95% CI, 2.7–13.3%). There is no significant difference between the fluorescent intensity of antibody response to PvMSP1-19 and PvMSP1-42 in the positive sera samples ( P > 0.05). The novel protein array platform may be used for profiling naturally acquired humoral immune responses to P. vivax infection.